Kausalitas Penerimaan, Pengeluaran dan PDRB Provinsi di Indonesia - Alno Sardi Putra; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This study has three main objectives, namely, first to find out how the causal relationship between local government revenue and local government expenditure in provinces in Indonesia, the second objective is to find out how the causal relationship between local government expenditure and GRDP in provinces in Indonesia. Meanwhile, the third objective is to determine the causal relationship between local government revenue and GRDP in provinces in Indonesia. In this study, the objects in this study are 33 provinces throughout Indonesia. The data used are from 2010 to 2019. The data used are secondary data obtained from the Central Statistics Agency (BPS). The analytical method used is the Granger clauseality test which is processed using Eviews. Based on the results of hypothesis testing, it shows that: (1) There is a reciprocal causal relationship between local government revenues and regional government expenditures in provinces in Indonesia in the western region. Thus the hypothesis is accepted. (2) There is a reciprocal causal relationship between local government revenues and local government expenditures in provinces in Indonesia in the eastern region. Thus the hypothesis is accepted. (3) There is no causal relationship between local government expenditure and GRDP, but there is a relationship between GRDP transfer and expenditure in 33 provinces in Indonesia in the western region. Thus the hypothesis is rejected. (4) There is no causal relationship between local government expenditure and GRDP, but there is a relationship between GRDP transfer and expenditure in provinces in Indonesia in the eastern region. Thus the hypothesis is rejected. (5) There is no causal relationship between GRDP and local government revenues in provinces in western Indonesia. However, there is a one-way relationship between government revenue and GDP. Thus the hypothesis is rejected. (6) There is no causal relationship between GRDP and local government revenues in provinces in eastern Indonesia. However, there is a one-way relationship between government revenue and GDP. Thus the third hypothesis is rejected